Urban cybernotopics: The flow pattern - Gaevskaya, Zlata (project baikal, 2023)
At the beginning of the 21st century the world has moved into the phase of global restructuring characterised by large-scale crises of life organization and science. For any science it is important to investigate the methodology of its cognition. Architecture and urban planning are no exception. The current commercial and industrial civilisation is built upon Western European positivism based on individualism, for which it is important how phenomena occur, not why they occur. The alternative to such a vision is a cosmic worldview based on the search for a genetic, eternal and always consistent connection between humans and nature in the space of the biosphere. The current instrumental and technical progress should be replaced by an organic progress that considers man and nature in a single connected Co-existence. This approach dictates a new urban planning in the perspective of cybernotopics, which considers the triad “nature – population – economy” as a flow pattern – the phenomenon of synchronicity in the dynamic, changeable, mobile equilibrium in the space of the biosphere. The technical external process of the impact on nature should be replaced by an organic process.